Hydrophobic species-enabled acid–base multi-catalysis for stereoselective access to renewable trans-anethole. Issue 43 (24th October 2022) - Liu, Yixuan; Li, Mingrui; Liu, Tengyu; Tan, Jinyu; Rokhum, Samuel Lalthazuala; Zhang, Heng; Yang, Song; Li, Hu
Abstract : A green and sustainable route was developed to stereoselectively produce biomass-based trans -AN (90% selectivity) over an acid–base bifunctional catalyst through cascade transfer hydrogenation and dehydration. Abstract : trans -Anethole ( trans -AN) is widely applied in food, daily necessities, and pharmaceuticals and is typically available from inefficient natural oil extraction or complex organic transformations over mineral acid or noble metals. Here, a green and sustainable route was developed to stereoselectively produce trans -AN ( ca. 90% selectivity) over an organic polymeric phosphonate–hafnium catalyst (PAS–Hf) through the cascade transfer hydrogenation and dehydration of biomass-based 4′-methoxypropiophenone (4-MOPP), with an environmental impact factor ( E -factor) of 47.73. The porous structure and the enhanced hydrophobicity of the spherical catalyst PAS–Hf ensured the formation of more accessible and stable Lewis (Hf 4+ ) and Brønsted (SO3 H) acid active sites, which could be used for rapid conversion of biomass-based 4-MOPP to AN (100% conversion, 97.2% yield) in 0.5–2 h (TOF: 9.3 h −1 ). Density functional theory (DFT) calculations elucidated that the addition of PAS–Hf could remarkably facilitate the overall conversion process by decreasing the reaction energy barrier (151.33 to 48.27 kJ mol −1 ) of the rate-determining step. The good thermal stability and heterogeneity of the bifunctional catalyst were responsible for its constant activity during at least five consecutive cycles. The synergistic/relay catalysis of Lewis acid–base and Brønsted acid species could be extended to more than ten kinds of aldehydes and ketones. This acid–base multi-catalytic protocol has considerable potential in cascade biomass conversion via heterogeneous catalysis without any base additive.